Ethical Issues in Public Health Nursing - Oberle, Kathleen (Nursing ethics, 2000)
This qualitative study was designed to explore ethical issues in public health nursing in the Canadian context, and to begin to identify strategies to support ethical practice. Twenty-two public health nurses, 11 in rural and 11 in urban settings, were asked to describe ethical problems they had experienced in the course of their work. These participants most often described situations that required a relational response rather than an active choice between options. Their goal was to optimize the good, while at the same time maintaining a supportive relationship. Analysis revealed five interrelated themes, each with several subthemes: relationships with health care professionals; systems issues; character of relationships; respect for persons; and putting self at risk. It was clear that all aspects of public health nursing have ethical components.